MBKM Curriculum Management at Universitas Negeri Manado - Delli Sabudu; Deitje A Katuuk; Sjamsi Pasandaran; Donal M Ratu (CV. Ridwan Publisher, 2023)
The purpose of this research is to analyze and describe the independent learning curriculum management model at Manado State University. Independent learning curriculum management is a form of curriculum management with the stages of planning, organizing, implementing and evaluating. The results of the study show that the independent curriculum management model at Manado State University has been implemented according to management functions, namely planning, organizing, implementing and evaluating. Of the nine study programs sampled that met the requirements, there were four study programs with a curriculum management model that were close to fulfilling the management function, although there were system constraints that were not yet available regarding the synchronization of courses between study programs and menus for MBKM contracts. In addition, the constraints related to human resources are still low knowledge about the implementation of independent curriculum management and the low interest of students to participate in MBKM activities